The Digital Classroom via LINE Application about Using TikTok for Marketing for Student with Intellectual Disabilities, School for the Deaf, Surin Province - Sopian, Thippawan; Khongchudi, Phonphimon; Maleekaew, Pintong; Srisakaew, Ubonwan; Lakonpol, Thongmee; Tasuntia, Jeeranun; Hiranrat, Wiphasith (Journal of Computer and Creative Technology, 2025)
This paper aimed to achieve four objectives: (1) to develop a digital classroom via the LINE application on the topic of using TikTok for marketing for individuals with intellectual disabilities at the School for the Deaf in Surin Province, (2) to evaluate the effectiveness of the developed digital classroom, (3) to study the learning achievement regarding the use of TikTok for marketing, and (4) to assess the TikTok marketing content creation skills of individuals with intellectual disabilities. The sample group consisted of 10 upper secondary students from the School for the Deaf in Surin Province, selected through purposive sampling. Research tools included online instructional media, a pre-test, a post-test, and skill exercise. Data analysis used the Wilcoxon signed-rank test and percentage calculations. The results showed that the digital classroom via the LINE application had an effectiveness score of 1.51, exceeding the Meguigans’ benchmark. Students demonstrated significantly higher learning achievement after the lesson at the 0.05 level of significance. Moreover, students with intellectual disabilities who learned through the digital classroom achieved a TikTok content creation skill level of 65.9%, which meets the hypothesis threshold of 50%.